2011
DOI: 10.4049/jimmunol.1004117
|View full text |Cite|
|
Sign up to set email alerts
|

TNF Mediates the Sustained Activation of Nrf2 in Human Monocytes

Abstract: Modulation of monocyte function is a critical factor in the resolution of inflammatory responses. This role is mediated mainly by the production of TNF-a. Investigations of the actions of TNF have mostly focused on acute activation of other cell types such as fibroblasts and endothelial cells. Less is known about the effects of TNF on monocytes themselves, and little is known about the regulation of cell responses to TNF beyond the activation of NF-?B. In this study, we investigated the regulation of NF-E2–rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 36 publications
(43 reference statements)
3
56
0
Order By: Relevance
“…As stimulus continues, increased inflammatory mediators (reactive oxygen species, TNF-α, prostaglandins and derivatives) might activate NADPH oxidase and Nrf2 to control the monocytes and macrophages. Recently, Atuart et al found that TNF induced TNF up-regulation by an autocrine mechanism to modulate prolonged Nrf2-induced gene expression, to protect against inflammatory impairment [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As stimulus continues, increased inflammatory mediators (reactive oxygen species, TNF-α, prostaglandins and derivatives) might activate NADPH oxidase and Nrf2 to control the monocytes and macrophages. Recently, Atuart et al found that TNF induced TNF up-regulation by an autocrine mechanism to modulate prolonged Nrf2-induced gene expression, to protect against inflammatory impairment [26].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some cell wall components of bacteria, such as lipoteichoic acids and lipopolysaccharides, were reported to activate the basic leucine zipper transcription factor NF-E2-related factor 2 (Nrf2), a key factor involved in antioxidant protein expression in human tracheal smooth muscle cells and monocytes [24]. Activation of Nrf2 induces the expression of various phase 2 detoxification genes, such as glutamate-cysteine ligase catalytic subunit, glutathione reductase, heme oxygenase-1 (HO-1) and NAD(P)H:quinone oxidoreductase 1 (NQO1), to protect against the deleterious effects of inflammatory actions [25], [26]. In monocytes, Nrf2-induced HO-1 and NQO1 expressions inhibit excessive proinflammatory cytokine secretion in response to lipopolysaccharides [27].…”
Section: Introductionmentioning
confidence: 99%
“…For example, mutated C/EBP␣, which defines a subgroup of acute myeloid leukemia (approximately 10% of all AML), has the capacity to displace HDACs from NF-B p50:p50 homodimers in unstimulated cells to activate NF-B target genes. 33,34 Other mechanisms of activity include the phosphorylation of ataxia telangiectasia mutated, a nuclear kinase that is required for NF-B activation and has been shown to be active in AML, 35 and constitutively active PI3-kinase/Akt, which activates downstream NF-B in AML. 36 Neither of these studies show a link to specific AML mutations or subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…U937 cells are monocyte-like cells that are known to not only secrete TNF-α but to also to become activated by TNF-α in a paracrine and autocrine fashion 49-52 . Thus, these cells provide a model system to study reciprocal interactions via the same secreted factor.…”
Section: Resultsmentioning
confidence: 99%
“…It is not unreasonable that secondary stimulation in the cells located downstream did not result in the same level of activation as the primary stimulation of cells located upstream. It is likely that mitogenic activation experienced by the cells located upstream elicits a much stronger cytokine response than the autocrine/paracrine stimulation experienced by the downstream cells 49 .…”
Section: Resultsmentioning
confidence: 99%